Other Popular Avenues For District Improvement: Using Asia To Assess Their Power - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
In reading through the district stories about using curriculum as a framework for improvement, many innovations were interwoven into ancillary efforts for curriculum development. As these are part of the stories of district curriculum development, we thought that discussions of these "ancillary efforts" were important. The innovations considered in this chapter are: Power standards, Professional learning communities, Common assessments, Data-driven decision making, and Walk-through's. We will consider these as if they were being implemented alone, and assess their power to produce student achievement gains using the ASIA framework. References to the district stories will be given. © 2014 by Nova Science Publishers, Inc. All rights reserved.
Journal Abbreviation: Curric.: Dist. Stories of a Path to Improv. Achiev.
Keywords: dept.edl